Implementation of the Village Financial System (Siskeudes) in Bandarjo Village - Aswin Fitriansyah; Mohamad Halilintar (PT Publikasiku Academic Solution, 2024)
This study aims to analyze the Implementation of the Village Financial System (SISKEUDES) on the government organization in Bandarjo Village, West Ungaran District, Semarang Regency. This research uses a qualitative research approach with primary data, namely interviews and secondary data. The informants are the village head, village secretary, and head of village government affairs. The results of the study show that: (1) The implementation of the Village Financial System in Suwaan Village has been running well (2) The procedures for utilizing SISKEUDES are carried out in 4 stages: Planning, Implementation, Administration, and Reporting (3) The Village Financial System has provided a positive influence on the performance of each employee. Therefore, the Village Financial System plays an important role in the village government directly impacted by village employees. This is in line with the purpose of implementing the Village Financing System, which is to assist the work of village employees.